Two rotator cuff tear repair techniques for sovraspinatus tendon tear: transosseous sharc-ft vs single row repair. : A prospective randomized study comparing two rotator cuff tear repair techniques for sovraspinatus tendon tear: transosseous sharc-ft vs single row repair. A clinical and radiological examination at two years follow-up - Pellegrini, Andrea; Baudi, Paolo; Rebuzzi, Manuela; Gialdini, Mauro (Acta Biomedica Atenei Parmensis, 2020)
Background: Despite rotator cuff repair techniques have developed significantly in last decade,pushed by the progress in technology and materials, the treatment of rotator cuff tears and re-tears is still abig challenge for shoulder surgeons. The aim of this study is to perform clinical and radiological evaluation(ultrasound and MRI) of patients treated with transosseous sharc-ft, and single row techniques forsovraspinatus rotator cuff tear at 6, 12 and 24 months follow up. Methods: Twenty-eight consecutive patientswho underwent arthroscopic repair for rotator cuff tear were enrolled in the study and divided in two differentgroups: group A (14 patients) underwent a single row technique repair; group B (14 patients) underwent atransosseous sharc-ft technique repair. All participants had MRI or ultrasound examination confirmed fullthickness tears of sovraspinatus tendon before surgery. All the patients underwent clinical evaluation at 45days, 3 months, 6 months, 12 and 24 months post-operatively with VAS, Dash, Constant and ASES score.Diagnostic ultrasound examination was performed at 6 months follow up while the MRI examination at1 and 2 year follow up. Results: The whole primary variables didn’t show any significant difference and thegroups were homogenous (age, Goutallier fatty infiltration, VAS, DASH, Constant, ASES). Some statisticallysignificant differences are visible at discrete variables in a specific time: Dash at 12 months and Constantat 24 months show a significant improvement versus single-row technique. Conclusion: The arthroscopictransosseous repair technique with sharc-ft showed excellent results with little significant statically differencebetween this technique and the single row for this kind of lesion after 1 year of follow-up. Clinical datafrom this study confirmed, with the help of ultrasound examination and MRI, the excellent clinical outcomeobtained by the patients. Further studies are needed to find differences between these techniques in the repairof large and massive rotator cuff lesions. (www.actabiomedica.it)